The Role of Heirs in Family Businesses: The Case of Carvajal (2009)
In this article we study why, contrary to international empirical evidence, CEO successions at Carvajal have been successful, although all the CEOs have belonged to the founding family. We develop a theoretical model which explains, given certain conditions, that the efforts of heirs can be similar to those of the founder and greater than outsiders'. We point out the importance of private knowledge, the non-monetary benefit of managing the firm, and the personal abilities, as determinants of the productivity achieved by family management.